A comida nas etnografias de festas religiosas: um estudo comparativo - Araujo, Fábio Francisco de (2025)
This dissertation aims to investigate the position, function, and meanings attributed to food in religious festivals that are part of devotional traditions within popular culture, based on ethnographic studies that focused on food as an important element in these celebrations. The research focused on seven selected ethnographic monographs, initially chosen from thesis and dissertation databases, which were expanded after the qualification stage. This study is structured in two parts. The first discusses the literature on food and eating in popular festivals. This section takes a more conceptual approach, aiming to build a framework for analyzing food contextualized within festivals, as outlined above. The second part is composed of two sections. The first section analyzes the focus on food in the ethnographies studied, seeking to understand how food participates in different stages of the ritual processes analyzed and how it becomes characteristic of each celebration. The second section presents a reflective analysis of the concepts and findings using the concept of ritual process, aiming to construct comparative frameworks that allow conclusions about the multiple meanings of food transformed into festive meals. In the festivals examined in this study, food represents a material element of the celebration, but it is also a symbol that encompasses meanings, forming part of the rite from preparation to the modes of consumption, as well as religious and social values. The typical food of these celebrations reveals itself as a structuring element of the ritual, bringing people together around shared practices that continuously reframe the festive experience and the sense of belonging.